Identification of the Microbial Population Found in Water Sources in and around San Salvador Island, Bahamas - Pelletier, Michel; Haynes, James M; Dungan, Ashley M; Kroeckel, John (International Journal of Bahamian Studies, 2014)
San Salvador Island in The Bahamas is home to approximately 1,200 people, and a popular vacation destination. In order to expand our knowledge of the bacterial population found on and around the island, and to assess possible health risks, we analyzed and identified the cultivable bacterial population found in several lakes and ponds throughout the island. The sites tested were located on the northern, north-eastern, eastern, and western districts, as well as one lake located inland. Ten sites with varying salinity, levels of oxygen, visibility, and distance from the ocean were analyzed. The nature of the bacteria present in these sites was identified by microscopy, as well as a series of biochemical tests based on bacterial metabolism. Seven bacterial species, predominantly from the genera Staphylococcus and Klebsiella were identified. Most bacteria identified are part of the normal microbiota of the skin and the gastro-intestinal tract of human and mammals, and should not be considered a danger for the health of the majority of the population and tourists of the island. We also isolated bacteria capable of fixing atmospheric nitrogen, a hallmark of marine bacterial populations. Overall, this study enabled us to add to the repertoire of bacterial species isolated and identified in the diverse marine environments found on San Salvador Island.